Invisible Fatherland Constitutional Patriotism in Weimar Germany - Achilles, Manuela (Cambridge Cambridge University Press, 2025)
List of Figures page; Acknowledgments; Prologue: Weimar Democracy Now and Then - A Perspective from Charlottesville; Introduction: Toward a New Paradigm of Weimar Democracy Studies; 1. From Kaiserreich to Reich; 2. 'Onwards over Graves'; 3. Symbolics of Shared Hegemony; 4. Anchoring the Nation in the Democratic Form; 5. Political Violence and the Inversion of Gewalt; 6. In Memoriam of Walther Rathenau; 7. Constitutional Patriotism Avant la Lettre; 8. Memory from Fragments; Conclusion: The Weimar Condition and Nazism; Bibliography; Index.
E-Book / Zugriff nur im Lesesaal